Production, consumption, marketed surplus and disposal pattern of milk in Andhra Pradesh - Lakshmipriya, Patibandla; R, Raju; Sirohi, Smita; Sankhala, Gopal; Chauhan, A K (Indian Journal of Dairy Science, 2019)
The present study investigated production, marketed surplus, consumption and disposal pattern of milk in Andhra Pradesh. The study covered 160 milk producers selected randomly from eight village dairy cooperatives which were post-stratified into small, medium and large herd size category. The study revealed that Overall average milk production was higher for member households (42.15 litres) as compared to non-member households (24.99 litres), respectively. Overall average milk consumption per day per household was lower in the member group (1.51 litres) than non-member group (2.06 litres), respectively. The average quantity of marketed surplus of milk per day per household was higher in the member group (40.64 litres) as compared to the non-member group (22.93 litres), respectively. Out of total quantity of milk disposed off per day by the member households, 96.21 per cent was disposed to dairy cooperatives followed by 2.84 per cent to milk vendors, 1.03 per cent to tea shops and only 0.91 per cent to consumers directly. Similarly, for non-member households, 80.50 per cent was disposed to dairy cooperatives followed by 12.88 per cent to private dairies, 2.49 per cent to milk vendors, 2.11 per cent to tea shops and only 2.03 per cent to consumers directly in the study area.